IMAGINED ISLAMIC SOCIETIES AND THE ROLE OF ULEMA IN CONTEMPORARY INDONESIA - Mahfud, Choirul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2019)
Abstract This article focuses discuss questions about how the role and contribution of ulema in the social life of religion in Indonesia. Also, how is the typology and characteristic of ulema in contemporary Indonesia. Sociologically, ulema is part of the most important topics in the study of religious institutions in the Islamic world, including when speaking about Islam in Indonesia. Ulema is also juxtaposed with umara. In this case, the position and role of the ulema are like an